Crystal growth in Ge-Sb-Se glass and its relation to viscosity and surface diffusion - Valdes Mitchell, Diego Alejandro; Martinková, Simona; Málek, Jiří; Barták, Jaroslav (Elsevier Science BV, 2021)
The crystal growth kinetics of Sb2Se3 in (GeSe2)x(Sb2Se3)1-x with compositions (x = 0.4, 0.5) were studied using infrared microscopy. Direct observation revealed two types of crystal growth during the overall process of crystal nucleation and growth: lateral crystal growth at the surface and crystal growth in the volume of the bulk sample (""volume crystal growth""). Both growth processes were studied in a wide temperature range within the frameworks of current crystal growth theories with respect to the transport of structural units from the amorphous phase toward the crystalline phase. The kinetic transport of structural units during the crystal growth can be described by viscosity in the case of volume crystal growth. Nevertheless, in surface crystal growth the transport of structural units deviates from viscous flow and is influenced by surface diffusion. The comprehensive analysis of relation between surface crystal growth, viscous flow and surface diffusion is given within this work.
Krystalový růst v Ge-Sb-Se sklech a jeho vztah k viskozitě a povrchové difuzi
Keywords: chalcogenides; crystal growth; viscosity; surface diffusion; chalkogenidy; růst krystalů; viskozita; povrchová difuze